Web-Based Asset Maintenance Monitoring System for CV Tartila Group : Sistem Pemantauan Pemeliharaan Aset Berbasis Web untuk Grup CV Tartila - Riyan Setiawan; Yuga nata praja; Wasis Haryono (NUANSA INFORMATIKA, 2026)
This study presents the development of a Web-Based Asset Maintenance Monitoring System for CV Tartila Group, a company engaged in photography, videography, and digital content production. Manual documentation of maintenance activities often leads to data loss, inconsistent records, and ineffective scheduling of preventive maintenance. The proposed system utilizes a structured approach based on the Waterfall Software Development Life Cycle (SDLC), covering requirements analysis, system design, implementation, and testing. The application integrates asset registration, maintenance history tracking, and automatic scheduling of preventive maintenance using a centralized MySQL database. The results of system testing show that the solution successfully replaces manual processes, increases the accuracy of service records, provides real-time monitoring, and improves decision-making regarding asset lifecycle management. This system contributes significantly to the operational efficiency of CV Tartila Group by reducing downtime and ensuring consistent asset performance